Analisis Strategi Pelayanan Kesehatan Pada Klinik Pratama Polres Nias - Siska Putri Kenangan Bunda Mendrofa; Syah Abadi Mendrofa; Odaligoziduhu Halawa; Delipiter Lase (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to analyze the health service strategy at the Nias Police Pratama Clinic. Health services are a crucial aspect for the police in supporting the health of personnel and the surrounding community. The method used in this research is a qualitative approach with data collection techniques through in-depth interviews, observation and documentation studies. The research results show that the Nias Police Primary Clinic faces several challenges in improving service quality, including limited medical facilities and equipment, a lack of health personnel, and the need to increase the implementation of standard operating procedures (SOP) such as 3S (smile, greet, greeting). However, challenges such as budget constraints and the need to improve medical technology remain obstacles. The service strategy aims to ensure that all individuals have equal access to necessary health services, while maintaining the sustainability of the health system. The Nias Police Pratama Clinic has developed various health service strategies that aim to meet the health needs of the Nias community effectively and comprehensively. The Nias Police Pratama Clinic faces various challenges in their efforts to provide optimal health services. By implementing the right strategy, it is hoped that the Nias Police Pratama Clinic can improve the quality of health services provided to personnel and the community.